Quantifying the impact of legal advice on households trajectories: what can we learn from administrative benefits data - Uraz, Juliet-Nil (International Journal of Population Data Science, 2025)
Objectives This research explores how administrative benefits data can assess the multidimensional impact of legal advice. By linking local authorities’ data with legal casework record, we bridge the evidence gap on legal interventions’ societal impact, translating insights into actionable strategies to improve outcomes for vulnerable populations facing social welfare disputes. Methods We use a mixed-methods approach, combining administrative data linkage with fieldwork, interviews, and surveys. Qualitative evidence informs a theory of change, identifying impact areas and underlying mechanisms. Retrospective matched control methods, adapted from healthcare evaluations, compare the socioeconomic trajectories of households receiving legal assistance with matched non-recipients over 24 months. Administrative benefits data, including the Council Tax Reduction Scheme, Single Housing Benefits Extract, and Universal Credit Data Share, provide monthly insights into financial and housing changes. Legal casework records detail the nature of legal problems and the intensity of the legal assistance, enabling heterogeneity analysis. Results Administrative benefits data provide a unique tool to track households’ welfare and housing outcomes post-intervention. By matching legal advice recipients with control households, we assess administrative data’s strengths and limitations in capturing legal services’ impact, such as benefits uptake or debt resolution. Preliminary findings show high overlap between legal service users and local welfare recipients, suggesting this vulnerable population is already in contact with local authorities before legal intervention and experiences significant housing insecurity and mobility. Qualitative insights highlight the importance of non-financial benefits’, such as improved legal confidence and wellbeing, which are invisible in administrative data. The study also underscores the role of independent third parties in data linkage research, fostering cross-sector partnerships, improving data-sharing practices, and strengthening operational data collection. Conclusions Harnessing administrative benefits data enables a data-driven approach to evaluating legal interventions. However, assessing preventive impacts in highly vulnerable populations presents challenges. Beyond evaluation, this research highlights how data collaborations strengthen infrastructures and foster data-driven cultures among resource-limited stakeholders. Co-designed projects can maximize administrative data’s potential to improve coordinated support.